UJI IN VITRO EKSTRAK AIR DAN ETANOL DARI BUAH ASAM GELUGUR, RIMPANG LENGKUAS, DAN KENCUR SEBAGAI INHIBITOR AKTIVITAS LIPASE PANKREAS - Iswantini, Dyah; Darusman, Latifah K.; Fitriyani, Ana (Badan Pengkajian dan Penerapan Teknologi, 2010)
Asam gelugur fruits of Garcinia often used to reduce body weight. Lengkuas and kencur are traditional herbal that potential for antiobesity because they could reduce the level of phospholipids, triglycerides, and cholesterol. The aim of the research was to evaluate the potencies of these herbal as antiobesity by measurement of their water and ethanol extracts capabilities as in vitro inhibitor of pancreatic lipase activity. The water and ethanol extracts of asam gelugur fruits contained saponins and alkaliods, respectively. The water extract of lengkuas rhizomes contained alkaloids, flavonoids, saponins, and quinones, while the ethanol extract contained alkaloids, flavonoids, saponins, and steroids. The water extract of kencur rhizomes contained saponins and quinones, while the ethanolextract contained alkaloids, flavonoids, steroids, and quinones. The highest inhibitory effect of all extracts was obtained from the ethanol extract of asam gelugur fruits with value of 86.3% at 150 ppm. The highest inhibitory effect of lengkuas extracts was from the ethanol extract at 200 ppm (56.2%). The highestinhibitory effect of kencur was showed by the ethanol extract with the value 37.6% at 300 ppm. These values were higher than the inhibitory effect of the positive control (Xenical®) at 100 ppm (10.6%).